Cubierta performática (2020)
Cubierta Performática aims to open the discussion around recovery processes of a lost social fabric through architecture. Taking to the conception of the project the people, their wishes and dreams. Seeing architecture as an opportunity to recover degraded spaces and links between inhabitants of a place is the premise of this thesis. Where through urban renewal it is intended to strengthen the notion of the public, the gradual reconstruction of both the relationships between individuals and individuals with the territory and strengthen the capacities of management and artistic creation.